ANALISA ASPEK HUKUM TERHADAP PERSETUJUAN PASANGAN HIDUP TANPA STATUS PERKAWINAN DALAM AKTA AUTENTIK: Indonesia - Ahmadi Ahmadi; Ahmad Imron (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
ABSTRACTThe more freely elements of western culture enter into the State of Indonesia or Indonesian people who have lived in western countries and now live in Indonesia by bringing western customs or culture about life partners who are not bound as husband and wife living together and those who are already have children without marital status. These rights to individual property are problematic in Indonesia. The regulations governing the approval of transfers, sales and debt agreements or credit agreements with the consent of the husband or wife in a notarized deed or authentic deed already have legal certainty where the agreement is due to be included in the joint property regulated in the Marriage Law Number: 1 of 1974 concerning marriage and amendments to Law Number: 16 of 2019 concerning amendments to the Marriage Law Number: 1 of 1974 concerning marriage, as well as the Civil Code or Civil Code. However, this research analyzes how from a legal aspect that occurs in practice in the field there are several parties who ask for the consent of a spouse who has no legal marriage ties to be included in an agreement with an authentic deed or a notarized deed with the argument of the parties as a form of guarantee of certainty so that can be known by the parties and if in the future there are no demands from their spouse. This research is a type of normative and empirical research, where research refers to legal norms and legislation as well as legal theories regarding the consent of a spouse and primary data which is carried out through interviews, by holding question and answer directly to the respondents. Agreement for a spouse without marriage ties in a legally valid agreement because it is the right of the parties based on the Civil Code Article 1338 paragraph (1) stipulates that